2021
DOI: 10.1111/1365-2656.13437
|View full text |Cite
|
Sign up to set email alerts
|

Sexual segregation in the foraging behaviour of a slightly dimorphic seabird: Influence of the environment and fishery activity

Abstract: 1. Sexual segregation in foraging strategies has been little studied in marine species with slight sexual size dimorphism (SSD), particularly regarding the role of environmental conditions and fishery activities. Sexual differences in fishery attendance are of particular concern because uneven mortality associated with bycatch may exacerbate impacts in wildlife populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Sex‐biased mortality rates due to by‐catch have been observed, especially in species that displayed sexual segregation (Bugoni et al., 2011). This could be problematic for our study since if one sex is more attracted to fisheries (as recently demonstrated in shearwaters; Reyes‐González et al., 2021), this could result in different areas used by sexes simply because of the distribution of fisheries fleets rather than natural ecological processes. However, a study recently demonstrated that male and female wandering albatrosses were similarly attracted by fisheries and found no evidence of competitive exclusion of females by larger males behind fishing vessels (Collet et al., 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Sex‐biased mortality rates due to by‐catch have been observed, especially in species that displayed sexual segregation (Bugoni et al., 2011). This could be problematic for our study since if one sex is more attracted to fisheries (as recently demonstrated in shearwaters; Reyes‐González et al., 2021), this could result in different areas used by sexes simply because of the distribution of fisheries fleets rather than natural ecological processes. However, a study recently demonstrated that male and female wandering albatrosses were similarly attracted by fisheries and found no evidence of competitive exclusion of females by larger males behind fishing vessels (Collet et al., 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In both Wandering Albatross and Giant Petrels, males and females seek different prey, causing them to segregate spatially (Phillips et al 2011). While such sex-specific segregation may not be as common in monomorphic seabirds (Hedd et al 2014), such segregation while raising chicks has been shown in the slightly dimorphic Scopoli's Shearwater Calonectris diomedea during environmentally challenging breeding seasons (Reyes-Gonzalez et al 2021). Under such conditions, both sexes increased foraging effort, but females travelled farther and expanded their Degree of overlap in searching locations between male and female Leach's Storm Petrels tracked with GPS at five different colonies in eastern North America between 2016 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 ), such segregation while raising chicks has been shown in the slightly dimorphic Scopoli's Shearwater Calonectris diomedea during environmentally challenging breeding seasons (Reyes‐Gonzalez et al . 2021 ). Under such conditions, both sexes increased foraging effort, but females travelled farther and expanded their foraging range beyond that of males, which the authors interpreted as competitive.…”
Section: Discussionmentioning
confidence: 99%
“…The Adriatic Sea, where the shearwater colony of Tremiti is located, is also an important area for the bottom trawl fishery of demersal species (M. barbatus, M. merluccius, Nephrops norvegicus). Although the natural diet of pelagic seabirds including Scopoli's shearwaters does not include demersal species, it is well known that they can have easy access to novel food resources scavenging on demersal fishes discarded by fishing vessels (Reyes-González et al, 2021). There is indeed evidence suggesting that also Scopoli's shearwaters from the Central Mediterranean scavenge on discards (Michel et al, 2022) and interact with fishing vessels (Cecere et al, 2015;Cianchetti-Benedetti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%